Isolation and identification of pathogenic bacteria present in wastewater effluents discharged into Lake Victoria at Mukuuba landing site, Wakiso district, Uganda. A cross-sectional study. - Seldon, Duluga; Kasozi , James; Lujjibirwa, Fortunate; Manowa , Daniel; Wanambwa Wamono, Herbert; Akena , John Baptist; Situma, Christopher; Ssentongo, Vianney; Muzoora, Saphan; Kyosiimire, Jacqueline; Sulwa, Florence; Nteziyaremye , Jorome; et al. (Student's Journal of Health Research Africa, 2025)
Background Wastewater effluents discharged into Lake Victoria often contain pathogenic bacteria that threaten aquatic ecosystems and public health. This study aimed to isolate and identify the pathogenic bacteria present in wastewater effluents discharged into Lake Victoria at Mukuuba Landing Site, Wakiso District, Uganda. Methodology The study employed a descriptive, cross-sectional, laboratory-based design and quantitative methods. A total of 30 wastewater effluent samples, purposively selected, were described using standardized microbiological techniques. Microsoft Excel 2016 was used to analyze data. Results Citrobacter freundii was the most frequently isolated organism (75%), followed by Enterococcus faecalis (64.29%). Staphylococcus aureus and Escherichia coli accounted for 17.86%, while Klebsiella pneumoniae (10.71%) and Proteus mirabilis (7.14%) were the least amount isolated. 70% of isolates were Gram-negative rods consistent with enterics from fecal contaminant (pink bacilli in histological image). The remaining 30% were Gram-positive cocci (purple clusters or chains), suggestive of Staphylococcus and Enterococcus species, respectively. Conclusion Contamination of effluent water has the potential for serious public health risks, and there is a significant risk contribution from these bacteria in wastewater effluents. Recommendation There should be an ideal surveillance of environmental health programs at a national level, by the Ministry of Health, to put in place the appropriate action for public health in risk zones.